The Passive Leg Movement Technique for Assessing Vascular Function: Defining the Distribution of Blood Flow and the Impact of Occluding the Lower Leg - Shields, Katherine L. (Exp Physiol, 2019)
It has yet to be quantified how passive leg movement (PLM)-induced hyperemia, an index of vascular function, is distributed beyond the common femoral artery (CFA), into the deep femoral (DFA) and the superficial femoral (SFA) arteries, which supply blood to the thigh and lower leg, respectively. Furthermore, the impact of cuffing the lower leg, a common practice, especially with drug infusions during PLM, on the hyperemic response is, also, unknown. Therefore, PLM was performed with and without cuff-induced blood flow (BF) occlusion to the lower leg in 10 healthy subjects, with BF assessed by Doppler ultrasound. In terms of BF distribution during PLM, of the 380±191ml of blood that passed through the CFA, 69±8% was directed to the DFA, while only 31±8% passed through the SFA. Cuff occlusion of the lower leg significantly attenuated the PLM-induced hyperemia through the SFA (~30%), which was reflected by a fall in BF through the CFA (~20%), but not through the DFA. Additionally, cuff occlusion significantly attenuated the PLM-induced peak change in BF (BF(Δpeak)) in the SFA (324±159 to 214±114 ml/min), which was, again, reflected in the CFA (1019±438 to 833±476 ml/min), but not in the DFA. Thus, the PLM-induced hyperemia predominantly passes through the DFA and this was unaltered by cuffing. However, as a small fraction of the PLM-induced hyperemia does pass through the SFA to the lower leg, cuffing the lower leg during PLM should be considered to emphasize thigh-specific hyperemia in the PLM assessment of vascular function.